Measurement and analysis of adsorption isotherms of CO2 on activated carbon. (25th March 2016) - Singh, Vinod Kumar; Anil Kumar, E.
Abstract: In the present work CO2 adsorption isotherms of a commercially available activated carbon, Norit Darco type obtained from lignite granular material, were measured. Adsorption isotherms were measured at different temperatures 298 K, 308 K, 318 K and 338 K and over a pressure range of 0–45 bar using Sievert's type experimental setup. Experimental data of CO2 adsorption isotherms were modelled using Langmuir and Dubinin–Astakhov (D–A) isotherm models. Based on coefficient of correlation and normalized standard deviation it was found that D–A isotherm model was well suited with the experimental data of CO2 adsorption isotherms. The important thermodynamic properties viz., limiting heat of adsorption at zero coverage, entropy, Gibbs free energy and isosteric heat of adsorption as a function of surface coverage were evaluated using van't Hoff and Clausius–Clapeyron equations. These thermodynamic properties were indicating that CO2 uptake by activated carbon is a physisorption phenomenon. The adsorption isotherms data and the thermodynamic parameters estimated in the present study are useful for designing of an adsorption based gas storage systems.